Meningkatkan Hasil Belajar Siswa Melalui Metode Team Games Tournament (TGT) Pada Pembelajaran SKI Kelas V Di Sekolah MIS Al-Amin Tembung - Arlina Arlina; Devi Permata Sari; Dewi Safitri; Nuraisyah Nuraisyah; Suliatun Nisa (LPPM Politeknik Pratama, 2023)
This type of research is Classroom Action Research (CAR). The purpose of this study was to improve the PAI learning outcomes of grade V students of MIS Al-Amin Tembung through the application of the Team Games Tournament (TGT) type cooperative learning model. The subject of the research was class V, totaling 27 people, consisting of 13 boys and 14 girls. The research implementation followed the flow of PTK referring to Kemmis and McTaggart with the stages of pre-action, action, observation and reflection. This research was conducted in two cycles. The results of the implementation of cycle I learning showed that the average student score was 25.93. Then continued in cycle II by reflecting and improving on the shortcomings that occurred in cycle I. The results of the application of the TGT learning model in cycle II showed that the average student score was 87.78. The results of the application of the TGT model in cycle II show that the TGT model can improve the learning outcomes of grade V students of MIS Al-Amin Tembung.